2020
DOI: 10.1186/s13063-020-04494-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic pulmonary telerehabilitation protocol for patients affected by COVID-19, confined to their homes: study protocol for a randomized controlled trial

Abstract: Background: In December 2019, 27 cases of pneumonia, of unknown cause, were identified in the province of Hubei (China). The WHO declared the situation as a Public Health Emergency of International Concern, and it was finally declared a global pandemic on March 11, 2020. The Spanish Government obliges the entire population to remain confined to their homes, with the exception of essential basic services, to stop the spread of COVID-19. Home isolation implies a notable physical deconditioning. Telerehabilitatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 34 publications
0
31
0
4
Order By: Relevance
“…The single RCT found during the screening process, about exercise in COVID-19 was conducted with patients after recovered from COVID-19 [ 36 ], however, it was excluded because it was an exclusion criterion. Our research also found a published protocol for a future RCT about the exercise in patients affected by COVID-19 confined to their homes, which will contribute to increase the knowledge about exercise in this population [ 68 ].…”
Section: Discussionmentioning
confidence: 94%
“…The single RCT found during the screening process, about exercise in COVID-19 was conducted with patients after recovered from COVID-19 [ 36 ], however, it was excluded because it was an exclusion criterion. Our research also found a published protocol for a future RCT about the exercise in patients affected by COVID-19 confined to their homes, which will contribute to increase the knowledge about exercise in this population [ 68 ].…”
Section: Discussionmentioning
confidence: 94%
“… 50 , 74 There is also a pressing need to understand which patients, if any, benefit the most from telerehabilitation. 86 While there have been a number of telerehabilitation studies in COPD, 67 , 75 the contextual heterogeneity of these studies (including the type of intervention, the participants involved, and the health care system in which they were deployed) makes clinical implementation extremely challenging. 85 Since the introduction of telerehabilitation can be quite expensive, it is important to ensure that its implementation is grounded on sound clinical policy decisions and solid high-quality evidentiary data.…”
Section: Challenges and Unanswered Questionsmentioning
confidence: 99%
“…With stay-at-home orders issued throughout the nation, more people are discovering the convenience, efficacy, and other advantages of completing tasks remotely. Telerehab offers indirect contact between the clinician and the patient while offering the patient social interaction, access to their treating healthcare therapist, and psychological wellness, which may be interrupted as a result of physical isolation during the current circumstances [ 28 ].…”
Section: Reviewmentioning
confidence: 99%